Morocco : Staff Report for the 2001 Article IV Consultation. (IMF Staff Country Reports; Country Report, 2001)
Morocco has been able to establish macroeconomic stability and industrial country levels of inflation, despite adverse weather conditions and terms-of-trade developments. Executive Directors welcomed these developments, and stressed the need to reduce unemployment and poverty. They appreciated the robust banking system, and emphasized the need to tighten macroeconomic policies and accelerate structural reforms. They commended the efforts taken in improving the timeliness and dissemination of statistical data, and agreed to undertake a Report on the Observance of Standards and Codes on statistics.